Modeling and simulation of the drying process of jabuticaba shells (Myrciaria cauliflora) - Marsiglia, Wanda Izabel Monteiro de Lima (2021)
The present work aims to determine the physical-chemical composition and bioactive compounds of the fresh jabuticaba bark, perform its drying kinetics at three different drying air temperatures, adjust empirical and diffusive mathematical models to the experimental data, produce the powder and evaluate the effect of drying temperature on its composition. The fruits were harvested, washed and sanitized with sodium hypochlorite solution, then the fruits were manually pulped and the solid fractions, pulp, peels and seeds were separated. The jabuticaba peels were dried in an oven with air circulation at temperatures of 45, 50 and 55 ºC and a speed of 1.0 m/s. Curves of drying kinetics were constructed, represented by the ratio of water content to drying time in minutes, adjusting to the mathematical models of Handerson and Pabis, Logarithmic, Midilli, Page and Newton to the experimental data. The models were selected taking as a parameter the magnitude of the determination coefficient (R2) and the chi-square function (). Shortly after drying, the shells were crushed to obtain the powder, which was characterized before and after drying in terms of physical, chemical, bioactive compounds and antioxidant activity. Fresh jabuticaba peels showed high levels of total phenolic compounds and total tannins. The Midilli model stood out from the others for presenting the highest value of R2 (> 99%) and the lowest value of the chi-square function (<0.000327) for the three temperatures studied, especially for the 45 ºC. The drying kinetics of jabuticaba peels showed that the temperature influenced the process, and that the constant “k” increased with its elevation, and the time of the process decreased as a result of its increase. The temperature of 45 ° C ensured a greater preservation of the total phenolic compounds, total anthocyanins and total flavonoids of the powder of the jabuticaba peels, and can be an alternative as an ingredient in the elaboration of several products, among them: bread, cake, biscuit, yogurt and drink milk because it has a significant amount of these bioactive compounds.